Physiological responses of pears to exogenous ethylene and pre-harvest factors influencing post-harvest quality with reference to 'Forelle' and 'Packham's Triumph' pears - Du Toit, P. G. (Petrus Gerhardus) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--University of Stellenbosch, 2000.